Thank you for the opportunity to help you with your question!
cross multiply the denominators and the numerators, like this
-4a (a-17)=12 (a-17)
then open the brackets like this:
= -4a^2 + 68a = 12a-204
then, put like terms together to get
-4a^2 + 68a -12a + 204 = 0
to give you
-4a^2 + 56a + 204 = 0
divide all through by 4 to get:
-a^2 + 14a + 51 = 0
Change the sign on first root to get:
a^2 - 14a - 51 = 0
after this, use the various methods of solving quadratic equations, mainly the formula one.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?